Aerosol hygroscopic growth and the dependence of atmospheric electric field measurements with relative humidity - Silva, Hugo (2019)
A simple formulation is developed to model the influence of the aerosol hygroscopic growth in the dependence of the atmospheric electric field measurements with relative humidity. The formulation uses the Petters and Kreidenweis׳s model for the hygroscopic growth factor of aerosols with relative humidity and assumes that the ion–aerosol attachment coefficient is linearly proportional to the particle radius according to Gunn׳s calculation. A formula which describes the atmospheric electric field increase with relative humidity in the regime expected for the aerosols to grow hygroscopically is found; between 60% and 90%. It also relates the microphysical parameter of aerosol hygroscopicity, κ, with the macrophysical measure of the atmospheric electric field. Historical data of atmospheric electric field and relative humidity recorded in the meteorological station of Portela (near Lisbon airport, Portugal) are used to fit the model. The electrical measurements were done with a Benndorf electrograph and the 1980–1990 period was considered. Due to the high pollution levels the atmospheric electric field measurements were divided in four wind sectors, NW, NE, SE, and SW. The sector least affected by pollutant aerosols, NW, was used in the fitting and the goodness found is r2~0.97, the aerosol concentration number is ~3280 cm−3 and the hygroscopic growth parameter κ~0.094. These are very reasonable values consistent with an urban environment, which typically has high aerosol number concentration with small hygroscopicity. The limitations of the model are presented throughout the sections.